Assessment of clinical efficacy of nefopam hydrochloride in lumbar disc prolapse patients in secondary care hospital - Samarpana, Suligeri; Chamundeswari, Yerukala; Jagadeesh, K.; Venkatesh, C.; Vinod, G.; Kodiganti, Raghu (International Journal of Research in Medical Sciences, 2021)
Background: In this study assessing the efficacy of 30 mg of nefopam hydrochloride in lumbar disc prolapse patients. Methods: This was a prospective observational study. This study was carried out about 6 months in secondary care hospital. 100 patients are involved in this study. Patient documentation forms, visual analogue scale, patient counselling forms are the materials for this study. In this study patients visiting the Hospital with low back pain patients are included in the study. Pregnancy patients and failed back syndrome are excluded in the study. Results: In this study different age groups of patients as follows 21 patients in 20-30 years of age, 31 patients in 30-40 years of age, 37 patients in 40-60 years of age, 11 patients in 60-80 years of age. Percentage of pain relief of Nefopam hydrochloride drug therapy as follows, 23 patients in 10-20%, 16 patients in 20-40%, 38 patients in 40-60%, 16 patients in 60-80%, 7 patients in 80-100%. Assessing pain intensity in no. of patients after nefopam hydrochloride drug therapy are as follows 10patients has no pain, 28patients has mild pain, 34patients moderate pain, 15 patients has severe pain, 13 patients are worst pain. Conclusions: In current study demonstrated that the analgesic efficacies of nefopam hydrochloride in low back pain patients. Nefopam shows better action in mild, moderate, severe and worst pain. Nefopam shows high efficacy.